2018
DOI: 10.1634/theoncologist.2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Premature Clinical Trial Discontinuation in the Era of Immune Checkpoint Inhibitors

Abstract: Clinical trial completion is critical for new cancer therapies. Premature trial termination or withdrawal is common and impairs progress. This study assessed factors of early terminated/withdrawn oncology trials, focusing on trials with immune checkpoint inhibitors (ICI), and found that poor accrual represents the main cause of early cancer trial termination. Premature termination/withdrawal rate was not significantly lower in immune checkpoint inhibitor trials compared to other trials. The discussion herein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
1
24
2
Order By: Relevance
“…More recently, Khunger et al published a similar analysis, which focused on immunotherapy trials compared to other oncology drug trials. The authors did not find a significantly different withdrawal or termination rate of immunotherapy trials compared to all other systemic cancer therapy studies; in line with the previous data, the authors confirmed lack of accrual as the major reason for trial termination 4 …”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…More recently, Khunger et al published a similar analysis, which focused on immunotherapy trials compared to other oncology drug trials. The authors did not find a significantly different withdrawal or termination rate of immunotherapy trials compared to all other systemic cancer therapy studies; in line with the previous data, the authors confirmed lack of accrual as the major reason for trial termination 4 …”
Section: Introductionsupporting
confidence: 74%
“…We did not observe a general correlation of symptom-control interventions with completion or termination of trials, to the contrary, symptomcontrol interventions performed in a curative setting were associated with an increased chance of success in the multivariate model; again, in the univariate analyses, this association was only observed in nonindustry-sponsored trials. Trials conducted exclusively in the United States were at an increased risk of termination in the multivariate models; however, this observation may be due to a selection bias: It is likely that almost all Phase 3 US oncology trials are registered with ClinicalTrials.gov while trials conducted at other locations are primarily registered locally and those additionally registered with ClinicalTrials.gov might be structurally different from a random sample of (only) locally registered trials.It must be emphasized that the overall model performance of the predictive models was relatively poor; that is, although the models show that some factors are predictors of trial termination, an accurate prediction of trial termination is not possible with the analyzed combination of factors.Neither the aforementioned positive 3 nor the negative4 association of industry-sponsoring with trial termination was confirmed in our data set. We observed a similar distribution of completed and terminated trials irrespective of sponsorship (absolute difference: 1.8%).Trial recruitment rates, on the other hand, were considerably faster (>3 times) in industry-sponsored trials; this association was also observed in a multivariate model.…”
contrasting
confidence: 62%
See 3 more Smart Citations